Provitamin A Maize Development: A Strategy for Fighting against Malnutrition in Nepal - Shrestha, Jiban; Karki, Tika Bahadur (Our Nature, 2015)
This review paper briefly highlights the importance, challenges and opportunities for adoption of provitamin A rich maize, and potential breeding strategies suitable in the context of Nepal. The biofortified maize with provitamin A could be the convenient, cheaper, and easily accessible source of vitamin A. It can provide a cheap and sustainable form of vitamin A for its deficiency prone communities. Unavailability of suitable maize varieties rich in provitamin A and insufficient nutrition education to the consumers are the major challenges for adoption of provitamin A maize. The introduction, development and commercialization of provitamin A rich maize varieties in collaboration with national and international scientists, CG centers, multinational companies, I/NGOs, government agencies, and private sectors can help to fight against vitamin A induced malnutrition in Nepal. DOI: http://dx.doi.org/10.3126/on.v12i1.12256 Our Nature (2014), 12(1): 44-48